Distinct Spontaneous Brain Activity Patterns in Different Biologically-Defined Alzheimer’s Disease Cognitive Stage: A Preliminary Study - Zeng, Qingze; Luo, Xiao; Li, Kaicheng; Wang, Shuyue; Zhang, Ruiting; Hong, Hui; Huang, Peiyu; Jiaerken, Yeerfan; Xu, Xiaojun; Xu, Jingjing; Wang, Chao; Zhou, Jiong; et al. (Frontiers in Aging Neuroscience, 2019)
Background: Recently, National Institute on Aging-Alzheimer’s Association (NIA-AA) has proposed a biological definition of Alzheimer’s disease (AD): individuals with both abnormal amyloid and tau biomarkers (A+T+) would be defined as AD. It remains unclear why different cognitive status are present in subjects with biological AD. Resting-state functional magnetic resonance imaging (rsfMRI) has provided an opportunity to reveal the brain activity patterns in biologically-defined AD cohort. We aimed to investigate distinct brain activity pattern in subjects with existed AD pathology but in different cognitive stage. Method: We selected individuals with AD pathology (A+T+) and normal controls (A-T-) based on the cerebrospinal fluid (CSF) biomarkers. According to the cognitive stage, the A+T+ cohort was divided into three groups: 1)preclinical AD; 2)prodromal AD; and 3)AD with dementia. We compared spontaneous brain activity measured by a fractional amplitude of low-frequency fluctuation (fALFF) approach among four groups. Results: We found increased fALFF values in the right inferior frontal gyrus in preclinical AD stage, whereas prodromal AD patients showed reduced fALFF in the bilateral precuneus, right middle frontal gyrus, right precentral gyrus and postcentral gyrus. Within AD with dementia group, both hyperactivity (right fusiform gyrus, right parahippocampal gyrus/hippocampus and inferior temporal gyrus) and hypoactivity (bilateral precuneus, left posterior cingulate cortex, left cuneus and superior occipital gyrus) were detected. Conclusion: Distinct brain activity patterns were detected in different cognitive stage among the subjects defined as AD biologically. Our findings may be helpful to understand mechanisms leading to cognitive changes in the AD pathophysiological process.